Factors in Decision Making of Undergraduate Students in Further Study at Suan Dusit University - ริมผดี, วรรณพรรธน์; มุกดา, วิภาดา; ประภากรเกียรติ, ธิติมา; ศุภกิจโกศล, ภัทรานิษฐ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
This research aim 1) to study factors in the decision making in further study at Suan Dusit University, 2) to compare the decision making factors in further study at Suan Dusit University based on personal data of students, and 3) to recommend the development of strategic approach of the new students admission at Suan Dusit University. The results found that: In overview, the decision making factors of students were at a high level. Considering in each aspect, the level of decision making factors from 1) the image aspect, 2) the staff aspect, 3) the physical aspect, 4) the services process aspect, and 5) the marketing promotion, 6) the study costing aspect, and 7) the location aspect was moderate. The results of decision making based on genders were not different with significant statistic level at 0.05. The development strategic approach of the new student’s admission in 7 aspects: 1. The image aspect, Suan Dusit University should create an identity column distinguished on the basis of excellence. 2. The study fees were in accordance with the structure of the newly formed division. 3. The location aspect was suitable and comfortable. 4. The marketing promotion is strategic planning and external relations for targeted groups efficiently. 5. The staff aspect, focuses on developing academic and support staff were to promote knowledge and expertise. 6. The services process is available through electronic media. 7. The physical aspect, the center of excellence is linked to knowledge and innovation.